2016
DOI: 10.15252/embj.201593741
|View full text |Cite
|
Sign up to set email alerts
|

Functional role of TRIM E3 ligase oligomerization and regulation of catalytic activity

Abstract: TRIM E3 ubiquitin ligases regulate a wide variety of cellular processes and are particularly important during innate immune signalling events. They are characterized by a conserved tripartite motif in their N‐terminal portion which comprises a canonical RING domain, one or two B‐box domains and a coiled‐coil region that mediates ligase dimerization. Self‐association via the coiled‐coil has been suggested to be crucial for catalytic activity of TRIMs; however, the precise molecular mechanism underlying this obs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
233
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 151 publications
(252 citation statements)
references
References 52 publications
12
233
2
Order By: Relevance
“…The overall architecture of the RING1/UbcH7 interface is similar to those in other RING/E2 pairs (Brown et al., 2014, Brzovic et al., 2003, DaRosa et al., 2015, Dou et al., 2012, Koliopoulos et al., 2016, Lechtenberg et al., 2016, Li et al., 2015, Plechanovova et al., 2012, Pruneda et al., 2012, Scott et al., 2014, Xu et al., 2008, Zheng et al., 2000). UbcH7 residues from loops 4 and 7 and helix 1 and HHARI RING1 residues from both Zn 2+ loops and the central helix make canonical E2/RING interactions (Figures 3A and S1A).…”
Section: Resultsmentioning
confidence: 99%
“…The overall architecture of the RING1/UbcH7 interface is similar to those in other RING/E2 pairs (Brown et al., 2014, Brzovic et al., 2003, DaRosa et al., 2015, Dou et al., 2012, Koliopoulos et al., 2016, Lechtenberg et al., 2016, Li et al., 2015, Plechanovova et al., 2012, Pruneda et al., 2012, Scott et al., 2014, Xu et al., 2008, Zheng et al., 2000). UbcH7 residues from loops 4 and 7 and helix 1 and HHARI RING1 residues from both Zn 2+ loops and the central helix make canonical E2/RING interactions (Figures 3A and S1A).…”
Section: Resultsmentioning
confidence: 99%
“…26). We did not observe a dimer of TRIM56 RING in our crystal structure, raising the possibility that SopA binding may interfere with TRIM56 RING dimerization.…”
Section: Discussionmentioning
confidence: 99%
“…Multiple studies demonstrated that the coiled-coil of various TRIMs mediates anti-parallel dimer formation21222324. Furthermore, catalytic activity of TRIM proteins is enhanced by coiled-coil-dependent dimerization and, more recently, was shown to require RING domain dimerization for the proper activation of the E2∼Ub conjugate2526.…”
mentioning
confidence: 99%
“…2016). This self-association enhanced E2 activity in discharge assays, consistent with what has been shown for other dimeric E2s, namely that this RING multimer stabilizes a closed-conformation of ubiquitin-loaded E2 conjugating enzymes (Dou et al.…”
Section: Trim E3 Ligases In Immune Signalingmentioning
confidence: 99%